Series solution with Frobenius method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
T In this article we explained the structure of Frobenius method to solve a homogeneous linear differential equations of order two . In any homogeneous linear differential equations of order two we have three cases of two roots ( as a ,b ) of the indicial equation :Case1 :  such that  where  is integer number and  . Case 2 :  . Case 3 :  , such that   . And we explained how to find the general solution of each case with many examples .